2010
DOI: 10.1007/s11814-010-0324-2
|View full text |Cite
|
Sign up to set email alerts
|

H3PW12O40/SiO2 for sorbitol dehydration to isosorbide: High efficient and reusable solid acid catalyst

Abstract: Tungstophosphoric acids (PW) supported on various metal oxides (SiO 2 , γ-Al 2 O 3 , TiO 2 , ZrO 2 and CeO 2 ) were synthesized and used as catalysts for sorbitol dehydration to isosorbide for the first time. 30% PW/SiO 2 exhibited the best catalytic performance for sorbitol dehydration, over which 56% isosorbide selectivity could be gained at a 95% sorbitol conversion at 250 o C. The catalytic performance of regenerated 30% PW/SiO 2 catalysts by dichloromethane elution showed no loss after recycling five runs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 19 publications
1
31
0
1
Order By: Relevance
“…[4] The reaction can be performed by using homo-or heterogeneous acidic catalysts such as those reported by Sun et al, who used a silicasupported heteropolyacid. [27] Yamaguchi et al have reported catalyst-free dehydration at elevated temperatures in water to obtain isosorbide in high yields. [28] They ascribed the success to the higher concentration of hydronium and hydroxide ions at higher temperatures owing to the temperature-dependent autoprotolysis of water.…”
Section: Isosorbide Production From Biomassmentioning
confidence: 99%
“…[4] The reaction can be performed by using homo-or heterogeneous acidic catalysts such as those reported by Sun et al, who used a silicasupported heteropolyacid. [27] Yamaguchi et al have reported catalyst-free dehydration at elevated temperatures in water to obtain isosorbide in high yields. [28] They ascribed the success to the higher concentration of hydronium and hydroxide ions at higher temperatures owing to the temperature-dependent autoprotolysis of water.…”
Section: Isosorbide Production From Biomassmentioning
confidence: 99%
“…For example, Li et al [50] observed deactivation of tungstated zirconia (fixed bed reaction at 245°C, 15%WO 3 -ZrO 2 ) while Weingarten et al [60] did not observe modification of the tungstated zirconia during the post-test analysis of the fructose dehydration (reaction in batch reactor at 160°C: 15%WO 3 -ZrO 2 ). Sun et al [61] deposited phosphotungstic acid particles (H 3 PW 12 O 40 ) on different non-acidic supports to convert sorbitol into isosorbide.…”
Section: Acidic Solidsmentioning
confidence: 99%
“…Development of non-hazardous synthetic methodologies for organic reactions is one of the latest challenges to organic chemists. Now, there is a need to develop new methodology in all areas of chemistry, like use of catalysts in organic synthesis process, and the growing concern for environmental demands the development of eco-friendly and economic processes wherein even less hazardous byproducts are not desirable, for example the use of high efficient and reusable solid acid catalyst such as H 3 PW 12 O 40 /SiO 2 for sorbitol dehydration to isosorbide [21], H 3 PW 12 O 40 /CeXZr 1−X O 2 catalysts [22], and ultrasound in chemical processes [23].…”
Section: Introductionmentioning
confidence: 99%